Studi Optimalisasi Perparkiran dan Pedestrian di Fakultas Teknik Jurusan Teknik Mesin, Teknik Elektro, Teknik Kimia dan Teknik Geofisika Universitas Lampung - Gustiaji, Laedo; Herianto, Dwi; Hadi, Yohanes Martono (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This study aims to determine the parking needs, determine whether the facility is adequate parkingand pedestrian, analyzing pedestrian handling solutions that are safe and comfortable in theFaculty of Engineering Department of Electrical Engineering, Mechanical Engineering, ChemicalEngineering and Engineering Geophysics.Intake of survey data on the number of vehicles and the number of available parking plots. Dataprocessing is done by analyzing the duration of parking, parking capacity, accumulation ofparking and parking index.Based on the survey and analysis of parking needs for this location is the car lands I and II of210% / day, for cars Land III by 19% / day, for motorcycle land I and II at 321% / day, for themotorcycle land III 81% / day. Thus, the index value above 100% of parking, which showed thatthe number of existing parking plots can not accommodate vehicles parked.Keywords: Transport, parking, pedestrian